Transforming Leadership Pathways for Humanities Professionals in Higher Education - Hentschell, Roze (Purdue University Press, 2023)
This collection of 14 essays investigates how humanities teacher-scholars grapple with the opportunities and challenges of leadership positions and connect them with their teaching and research endeavors. It makes space for serious conversation about the multiple roles many humanities specialists play and offers strategies for professional growth, sustenance, and satisfaction. The collection also considers the relationship between our disciplinary areas of study, our academic training, and the lives we inhabit and aspire to. The collection?s research-inflected essays address diverse types of institutions and leadership positions and speak to lived experience in them. While we emphasize that a leadership path in higher education can be a welcome and positive professional move for many humanities professionals, our volume also acknowledges the issues that arise when faculty take on administrative positions while otherwise marginalized on campus, either by virtue of faculty status, rank, or personal identities.